KONFLIK ANTARA MENANTU PEREMPUAN DAN IBU MERTUA DALAM SUKU BATAKYANG TINGGAL SERUMAH DI DESA KARYA INDAH KECAMATAN TAPUNG KABUPATEN KAMPAR - Nadeak, Delty Septywaty; ", Syafrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study was conducted at Desa Karya Indah Kecamatan Tapung Kabupaten Kampar. The purpose of this study is to know knowing the trigger factor of the occurrence of Conflict Between the In-laws of Women And Mother-In-House In Batak Tribe Living at Desa Karya Indah Kecamatan Tapung Kabupaten Kampar. The focus of this research is the form of conflict between the daughter-in-law and the mother-in-law in the Batak tribe who live at home at Desa Karya Indah Kecamatan Tapung Kabupaten Kampar. The technique of determining samples in a purposive sampling and set the number of samples as many as 5 people. The author uses qualitative descriptive method and Instrument data is observation, interview and documentation. Research conducted at Desa Karya Indah has been completed by drawing some final conclusions as follows: The forms of conflict between the in-laws and the law-in-law are Role Conflicts, the role conflict that occurs as a result of the expectation of a son-in-law and his father-in-law is inconsistent with his wish or reality, The pressure experienced by a son-in-law. Realistic conflict, the realistic conflict form of this research is the closed attitude of the in-laws, the views of the in-laws with the insensitivity of the inborn to the wishes of his father-in-law, Interpersonal Conflict, Interpersonal Conflict between law and law-in-law as the attitude of in-laws who still believe in the beliefs in the village, speaking son-in-law comes from a soft-spoken family but a determined in-laws, and an attitude of non-disclosure and distrust. Factor that triggered the conflict can be from the results of research that is done, the relation of big family, the relation between the couple, discomfort in the household. The inconvenience of research subjects in the household such as the controls that are at home in the hands of his father-in-law, and the kerisihan that occurred from the daughter-in-law due to interfere in-law in his household.Keywords: Conflict, Interpersonal, Interpersonal, Daughter, Factor